Practical guidelines for drug correction of diffuse dyshormonal dysplasia of the breast - I. V. Vysotskaya; V. P. Letyagin; Ye. A. Kim; N. V. Levkina (ABV-press, 2014)
Тhe article presents the current approaches the most common drug therapy diffuse breast pathology - dyshormonal dysplasia. The role and place the most effective use of the base herbal medicine as well as various options for different symptoms of hormonal correction.